"So many extra safety layers": virtual service provision and implementing social distancing in interpersonal violence service agencies during COVID-19 - Voth Schrag, Rachel J. (Journal of family violence, 2023)
The coronavirus pandemic necessitated rapid shifts in approach for service providers working with survivors of interpersonal violence. To reduce the spread of the virus, providers and agencies implemented a rapid and unplanned expansion of virtual services while also developing new protocols to support safe and socially distant in-person services. To understand how these shifts have impacted victim service professionals and the survivors they serve, to provide guidance for on-going efforts, and to inform planning for future public health emergencies, this study asks the question: What approaches did the interpersonal violence workforce use to address social distancing needs during COVID-19? Semi-structured interviews were conducted from July to December 2020 with 33 interpersonal violence service providers from across the United States, and data were analyzed via conventional content analysis with additional steps for data credibility. Findings fall within two primary categories: 1) Technology and Virtual Service Provision; and 2) Social Distancing for In-person Services. Within each category, a number of themes emerged illustrating strengths and challenges of each approach, and the complex web of technological, safety, and public health considerations being balanced in interpersonal violence service agencies. These results provide guidance for the implementation of virtual services in an on-going manner, as well as underscoring the importance of future planning to facilitate effective in-person but physically distant services. There is also a clear need for agencies to support the interpersonal violence workforce to reduce occupational stress and enhance skills and capacities with new forms of services.